Evolving Practice Patterns Over Two Decades (1993–2013) in the Management of Desmoid-type Fibromatosis in British Columbia. Issue 4 (April 2020) - de Bruyns, A.; Li, H.; MacNeil, A.; Simmons, C.; Clarkson, P.; Goddard, K.; Munk, P.L.; Hart, J.J.; Holloway, C.; Truong, P.; Feng, X.
Abstract: Aims: Due to the rarity and varied natural history of desmoid-type fibromatosis, evidence-based treatment standards for this disease remain lacking. This study evaluated outcomes in patients with desmoid-type fibromatosis managed at a Canadian institution over two decades. Materials and methods: Records of 227 patients with desmoid-type fibromatosis referred from 1990 to 2013 were retrospectively reviewed to investigate management strategies including active surveillance, surgery, radiation therapy, cryoablation, and systemic therapy, including tamoxifen and chemotherapy. Results: Thirty-two per cent of cases were men, median age 40 years, median tumour size 5.4 cm. Initial treatments were surgery (79%), tamoxifen (13%), radiation therapy (5.0%), chemotherapy (1.8%) and cryoablation (1.2%). Active surveillance was used upfront in 26% of cases, most after 2005. At a median follow-up of 77 months, one patient died of disease, 13 died of unrelated causes and the remainder were alive with no evidence of disease (56%), stable/responding disease (33%) or progressive disease (4%). The recurrence rate was 25% after upfront surgery. Response rates and disease control rates were 40% and 76% for active surveillance; 68% and 96% for radiation therapy; 31% and 67% for tamoxifen; and 53% and 80% for chemotherapy. On univariable analysis, factors associated with a higher recurrence after initial surgery were young age ( P = 0.012), male gender ( P = 0.012) and extremity location ( P = 0.005). On multivariable analysis, only young age was significantly associated with recurrence risk ( P = 0.010). Conclusions: Active surveillance was associated with spontaneous regression and long-term disease control consistent with other studies. Primary radiation therapy appeared to provide a similar response and disease control compared with systemic treatments and may be a viable option for patients who are not candidates for surgery or active surveillance. Highlights: Multidisciplinary outcome data from a large series at a Canadian institution. Active surveillance was associated with spontaneous regression and long-term disease control. Practice shift from upfront surgery to active surveillance was observed after 2005. Primary radiation treatment was at least as effective as systemic treatments. Radiation therapy is a viable option when active surveillance fails or when surgery is not recommended.